Geomechanical characteristics of gas shales: A case study in the North Perth basin - Rasouli, Vamegh; Sutherland, A. (Springer, 2014)
Gas shales are one type of unconventional reservoirs which have attracted significant attention for gas production in recent years. Gas production from very tight shales requires employment of hydraulic fracturing as a stimulation technique. To design hydraulic fracture operation the mechanical properties of the targeted and surrounding formations should be estimated. Also, the magnitude and orientation of in situ stresses in the field need to be known to estimate the fracture initiation and propagation pressures. This study focuses on gas shale characteristics in the North Perth Basin and uses data corresponding to well Arrowsmith-2 (AS-2) which is the first dedicated shale gas well drilled in Western Australia. A log-based analysis was used to build the rock mechanical model (RMM). The RMM results were used to set up a hydraulic fracturing laboratory experiment. The test was done in the presence of three principal stresses to mimic the real field stress conditions. The test results include the pressure–time curve which was used to estimate the initiation and propagation pressure at that depth. The results were used to draw some practical conclusions related to hydraulic fracturing operation in the field.